Modified useful-learning approach, student achievement, critical thinking and attitude in chemistry - Marasigan, Arlyne C. (2007)
This study was conducted to assess the effectiveness of the Modified Useful Learning approach against the traditional teaching approach in improving student achievement, critical thinking and attitude towards chemistry. Modified Useful Learning (MUL) approach is a combination of Learning-for-Use model developed by Edelson (2001) and Hypothetico-Predictive Reasoning by Lavoie (1999). Quasi-experimental pretest-posttest control-group design was used in this study. The sample consisted of two intact sections of junior students at Diliman Preparatory School, Quezon City. No significant difference was found between the scores in the Chemistry Achievement Test-Multiple_Choice (CAT-MC) of the MUL and traditional group.